Kształtowanie się siedzib niższych urzędników krzyżackich w Prusach Właściwych - Knyżewski, Marcel (Acta Universitatis Lodziensis. Folia Archaeologica, 2017)
So far, it Conventual castles were at the center of interest of researchers of Teutonic architecture. However, it seems that it slowly starts to change. Until recently, the seat of the Teutonic Knights lower officials, except the most distinctive constituted a complete research margin. Currently, there are at once numerous publications on individual objects, but we should also look at the subject more broadly and make placing them in specific political and economic realities. We are not able at the moment to say much about the thirteenth century buildings, which would constitute the seat of the Teutonic Knights lower officials to discussed area. It was not until the beginning of the fourteenth century brings more information about the existence of headquarters of minor officials. At this time, the evident revival building in the Zulawy. This is understandable due to the transfer of the seat of the great masters to Marienburg. Most of these assumptions was the auxiliary facilities of the capital castle. Very important are the 30s and 40s of the fourteenth century. On the east of the country are formed the quite numerous, probably wood and earth strongholds. Objects located in the western part of Prussia gain at this time bricked forms. A clear turning point for the sites are the Lithuanian army raids in the 60s and 70s the fourteenth century. After these events, some objects ceased to function (Okartowo) while others have been transformed into brick castles (Pisz). Additionally, in the western regions of Prussia, some assumptions have been expanded. But it was only after the signing of the armistice with Lithuania began to build castles on a much larger scale. Construction work lasted in many objects until the outbreak of the Great War. After it state’s economic situation has changed dramatically. There were mainly modernization works on castles.